Sea level and temperature extremes in a regulated Lagoon of Venice - Ferrarin, Christian; Bonaldo, Davide; Bergamasco, Alessandro; Ghezzo, Michol (Frontiers in Climate, 2024)
Increasing sea levels and water temperatures have been detected at several coastal locations worldwide with severe consequences on the communities and ecosystems. Coastal lagoons are particularly vulnerable to such changes due to their low land elevation and limited connections with the open sea. Here the recent and future climatic changes in the Lagoon of Venice (Italy) are investigated using in-situ observations and high-resolution hydrodynamic modelling. Trend analysis was applied to observed time series of meteorological and oceanographic climate essential variables to identify significant long-term changes in mean and extreme values. The mean relative sea level rose at a rate of 4.9 mm per year in Venice due to the combined action of eustacy and subsidence while air and sea temperatures increased on average by 1.8 and 1.1• C in 30 years, respectively. These rates, as well as climate projections, were used following a pseudo-global-warming approach to investigate the near future (up to 2050) evolution of the lagoon's dynamics focusing on sea level and temperature extremes. The lagoon will amplify the temperature changes expected for the Adriatic Sea, especially in the shallow tidal flats where the intensity of the marine heat waves will be more than four times larger than that in the open sea. Moreover, the model allowed us to perform "what-if" scenarios to explore to which extent the flood protection MoSE barriers will modify the lagoon's dynamics. According to the simulations, the number of floods and therefore of the MoSE closure strongly increases with sea level rise. In the most severe scenario, MoSE will have to close for more than 20% of the time in October, November and December resulting in the reduction of water exchange with the open sea and exacerbation of marine cold spells. Some considerations on the implications of the expected changes on the lagoon's ecology are proposed.